Using Earth Observations to Help Developing Countries Improve Access to Reliable, Sustainable, and Modern Energy - Leibrand, Amy; Sadoff, Natasha; Maslak, Tanya; Thomas, Amy (Frontiers in Environmental Science, 2019)
In this review paper, the authors identify priority areas and opportunities for electric utilities in developing and emerging economies to incorporate Earth observation (EO) data into rural electrification planning, renewable energy resource assessment, distributed generation, grid operation and reliability, and disaster risk reduction and recovery efforts. Using a methodological framework, the authors conducted a comprehensive literature review of primary and gray literature. This paper reviews the many existing applications for EO data, such as the use of nighttime lights imagery for estimations of rural electrification, EO-derived normalized difference vegetation index (NDVI) products for vegetation monitoring for overhead transmission line management, solar radiance data for renewable energy project planning, and nowcasting for extreme weather events and other disaster monitoring. These and other applications can enhance energy security through improved access to modern and reliable electricity, renewable energy management, and disaster risk assessment in developing nations, paving the way for more sustainable social and economic development. Real-world examples of EO data use by utilities in developing and emerging economies, as well as barriers and opportunities for EO technology transfer, are discussed. Recommendations for stakeholder engagement, future EO training opportunities, and human capacity building are also presented.